2018
DOI: 10.1029/2018jf004626
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Stresses Drive Damage of Alpine Valley Rock Walls During Repeat Glacial Cycles

Abstract: Cycles of glaciation alter the temperature field in proximal alpine valley flanks, driving rock slope damage through thermomechanical stresses. Here we extend simplified assumptions of glacial debuttressing to quantitatively examine how paraglacial bedrock temperature changes, acting in concert with changing ice loads during Late Pleistocene and Holocene glacial cycles, create damage in adjacent rock slopes and prepare future slope instabilities. When in contact with temperate glacier ice, valley walls maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 82 publications
5
63
0
Order By: Relevance
“…We adjusted assumptions in Grämiger et al (2017), assuming that joint set F1 (see Table 2) contains 15% (instead of 10%) rock bridges, set F3 contains 25% (instead of 20%) rock bridges, and intact rock represented by Voronoi contacts contains 100% rock bridges for HM models. The calculated rock strength properties listed in Table 2 resulted in an initial damage field that was similar (albeit not identical) to the studies of Grämiger et al (2017Grämiger et al ( , 2018 also including a similar ratio between shear-and tensile-mode failure.…”
Section: 1029/2019jf005494supporting
confidence: 52%
See 3 more Smart Citations
“…We adjusted assumptions in Grämiger et al (2017), assuming that joint set F1 (see Table 2) contains 15% (instead of 10%) rock bridges, set F3 contains 25% (instead of 20%) rock bridges, and intact rock represented by Voronoi contacts contains 100% rock bridges for HM models. The calculated rock strength properties listed in Table 2 resulted in an initial damage field that was similar (albeit not identical) to the studies of Grämiger et al (2017Grämiger et al ( , 2018 also including a similar ratio between shear-and tensile-mode failure.…”
Section: 1029/2019jf005494supporting
confidence: 52%
“…Our goal was to begin the simulations with similar initial damage conditions (here quantified as the cumulative length of failed joints) as in our preceding companion studies (Grämiger et al, 2017(Grämiger et al, , 2018 in order to facilitate comparison. Assuming the same rock strength properties while accounting for effective joint stresses, however, resulted in a greater amount of initial damage.…”
Section: 1029/2019jf005494mentioning
confidence: 99%
See 2 more Smart Citations
“…As glaciers are wasting down due to recent atmospheric warming, the lowest headwall sections are exposed to direct atmospheric forcing. Their formerly constant thermal regime is now disturbed by diurnal to annual temperature cycles, a transition recently termed 'paraglacial thermal shock' (Graemiger et al, 2018). A related long-term terrestrial LiDAR study from the Kitzsteinhorn found dramatically increased rockfall activity in recently deglaciated headwall sections and thus confirmed a pronounced paraglacial response (Hartmeyer et al, in preparation).…”
Section: Implications For Rock Slope Stabilitymentioning
confidence: 98%